Diretrizes para o design de jogos educacionais que incluam pessoas com Transtorno do Espectro Autista - Valério Neto, Luiz (2025)
Autism Spectrum Disorder (ASD) is characterised by difficulties in social interaction and communication, as well as repetitive patterns of behaviour. These difficulties significantly impact the ability to understand and engage in social and educational activities. Games have been explored as a powerful educational resource capable of promoting greater engagement in teaching-learning processes. However, few studies are dedicated to supporting the development of educational games that consider the needs of students with ASD following an inclusive design approach. In this context, this work aims to propose guidelines to support the design of inclusive educational games, focusing on promoting equivalent playful learning experiences for people with and without ASD. The main phases of this research are: (i) Systematic Literature Review (SLR) to identify and analyse the state of the art on the design of systems and games for people with ASD; (ii) definition of an initial set of guidelines for the design of inclusive educational games, focusing on the inclusion of students with ASD; (iii) design and implementation of an educational game using the proposed set of guidelines; (iv) evaluation of the guidelines and the developed game by Special Education experts; (v) application of the inclusive educational games developed in this research at schools, involving students with and without ASD; (vi) analysis of the results obtained from the application of the games and discussions with experts, for subsequent refinement of the guidelines and the games. Overall, the set of guidelines proposed in this research was able to assist developers in producing an inclusive educational game for people with and without ASD, promoting equivalent learning and fun experiences for both groups of students, without the need for a specific game version for students with ASD.